Transcriptional changes in the rat brain induced by repetitive transcranial magnetic stimulation - Weiler, Marina; Stieger, Kevin C.; Shroff, Kavisha; Klein, Jessie P.; Wood, William H.; Zhang, Yongqing; Chandrasekaran, Prabha; Lehrmann, Elin; Camandola, Simonetta; Long, Jeffrey M.; Mattson, Mark P.; Becker, Kevin G.; et al. (Frontiers in Human Neuroscience, 2023)
Introduction Transcranial Magnetic Stimulation (TMS) is a noninvasive technique that uses pulsed magnetic fields to affect the physiology of the brain and central nervous system. Repetitive TMS (rTMS) has been used to study and treat several neurological conditions, but its complex molecular basis is largely unexplored. Methods Utilizing three experimental rat models (in vitro, ex vivo, and in vivo) and employing genome-wide microarray analysis, our study reveals the extensive impact of rTMS treatment on gene expression patterns. Results These effects are observed across various stimulation protocols, in diverse tissues, and are influenced by time and age. Notably, rTMS-induced alterations in gene expression span a wide range of biological pathways, such as glutamatergic, GABAergic, and anti-inflammatory pathways, ion channels, myelination, mitochondrial energetics, multiple neuron-and synapse-specific genes. Discussion This comprehensive transcriptional analysis induced by rTMS stimulation serves as a foundational characterization for subsequent experimental investigations and the exploration of potential clinical applications.